Cocaine, the contras, and the United States: how the U.S. government has augmented America's drug crisis - Scott, Peter Dale (Crime, law and social change, 1991)
A study of Washington's connections to Honduran and other contra supporters in the illicit drug traffic shows that such gray alliances for covert operations are themselves a major part of this country's drug problem. It is true that the U.S. has arrested contra supporters on drug charges; but, time after time, these drug arrests have come after the U.S. has ceased to promote the contra faction which those arrested had been supporting. The new Bush drug strategy seems unlikely to affect the window of drug smuggling opportunity opened by Washington's relations with the corrupt Honduran military, and may well open new such windows by new grey alliances with the corrupt right-wing forces in the Andean countries of origin.Footnote 1